Leaf Spectral Indices for Assessing Physiological Traits in Dalbergia sissoo Seedlings - Alam, Badre; Chaturvedi, Mayank; Singh, Anil Kumar; Newaj, Ram (Indian Forester, 2016)
Photosynthetic traits are indicators of physiological status of plants and the measurement of photosynthetic traits are often time consuming and complex.Response of leaf to incident light largely determines its use in photosynthesis. Thus the spectral traits based on the reflectance of light by the leaf can be used to assess the physiological status of plants. This has immense significance for multiple purpose tree species (MPTs) as well. In case of MPTs, such traits can also be used to understand the mechanistic insight and acclimation strategies under changing climate. We have investigated some important leaf spectral traits related to the physiological functioning of Dalbergia sissoo which is an important MPTs grown throughout India. Leaf spectral indices like normalized difference vegetation index (NDVI), photochemical reflectance index (PRI), water balancing unit (WBU) and chlorophyll index (CI) in relation to some important photosynthetic and physiological traits have been assessed. Good correlations in all the above traits were observed. These correlations indicated that the selected spectral indices could be judiciously applied to understand intercellular functioning of plants non-invasively and it will be useful for interpretation of the photosynthetic and physiological status of plants undergiven climatic conditions.